(untitled) (Modern education and development, 2025)
This article explores the reasons behind humanity’s critical attitude towards itself and the pursuit of perfection from psychological, sociological, and cultural perspectives. The work explains the connection between evolutionary factors, the influence of modern social networks, and human needs. The author presents the argument that it is necessary to find a healthy balance between self-criticism and the pursuit of an ideal.